Implementation of Mind Mapping Method to Stimulate Creativity in Children Aged 5-6 Years - Setyowati, Ana; Kristiana, Dian; Rusdiani, Nurtina Irsad (Universitas Muhammadiyah Ponorogo, 2025)
This study aims to examine the implementation of the Mind Mapping method in stimulating the creativity of children aged 5-6 years at TK PKK Talun, Desa Talun, Kecamatan Ngebel, Kabupaten Ponorogo. The approach used is field descriptive qualitative. Data were collected through observation, interviews, and documentation involving 20 children, as well as teachers and parents. The results show that the Mind Mapping method is effective in enhancing children's creativity, as evidenced by the increase in creative thinking abilities such as generating new ideas and connecting concepts. Observations indicated that the children were more active and enthusiastic in learning activities. Interviews with teachers and parents revealed that this method helps children understand the material better and improves their memory. Documentation of the children's work showed improvements in uniqueness and innovation aspects. Based on these findings, the Mind Mapping method is recommended as a learning strategy to stimulate creativity in early childhood education at TK PKK Talun.